Characteristics of pain, other symptoms and function in pediatric post‐thrombotic syndrome. Issue 2 (15th April 2018) - Avila, Maria L.; Stinson, Jennifer; Lumia, Celeste; Williams, Suzan; Montoya, Madeline I.; Feldman, Brian M.; Brandão, Leonardo R.
Abstract: Essentials: Symptoms and function in pediatric post‐thrombotic syndrome (PTS) remain poorly characterized. Clinical features of PTS were studied in 78 children with history of limb deep vein thrombosis. Tired limb, heaviness, pain, and impaired endurance were the most frequent clinical findings. Frequency of symptoms and of impaired endurance were similar in upper and lower extremities. Pain was associated with the presence of other symptoms and impaired function. Background: Symptoms and function in pediatric post‐thrombotic syndrome (PTS) remain poorly characterized. Methods: The present cross‐sectional study describes the characteristics of pain, other symptoms, and impaired function in pediatric PTS in a cohort of children with history of upper or lower limb deep vein thrombosis and PTS diagnosis. The frequency of clinical findings was compared between patients with and without pain, and between patients with upper and lower extremity PTS. Results: Seventy‐eight children were included in the study. The most common PTS symptoms were pain, tired limb and heaviness. Symptoms were usually reported to occur at mid‐day or later and were typically triggered by exercise. Half the patients reported impaired endurance. Pain was reported by 45% of patients and was usually mild‐moderate. Heaviness, tightness, tired limb, paresthesia, self‐reported limb edema, and impaired endurance were most common in patients with than in patients without pain. Conversely, activity and participation scores, skin redness, and clinician‐assessed limb edema did not differ between patients with and without pain. Lastly, there was no difference in pain intensity or frequency of paresthesia, swelling, heaviness, or impaired endurance when comparing the upper and lower extremities. Conclusion: Tired limb, heaviness, pain, and impaired endurance were the most frequent clinical findings in pediatric PTS. Frequency of symptoms and pain intensity did not differ between upper and lower extremities. Pain was associated with the presence of other symptoms and impaired function, but not with activity limitation and participation restriction. Better tools are needed to measure these two latter aspects of health.